CLINICAL CRITERIA FOR THE DIAGNOSIS OF PEDIATRIC BRONCHIAL ASTHMA - Toledo, Rodolfo Ricardo; Alves, Alícya Freitas; Marques, Julia Rios Reis; Miranda, Maria Eduarda Beckman (Seven Editora, 2026)
Introduction: Pediatric bronchial asthma is a disease most prevalent in childhood, characterized by chronic airway inflammation and recurrent episodes of wheezing, dyspnea, cough, and chest tightness. It is a multifactorial condition, associated with genetic, environmental, and immunological factors – whose early diagnosis is essential to prevent persistent impairment of lung function in adulthood. Methodology: The study consists of a narrative literature review, based on scientific articles published between 2020 and 2026, obtained from databases such as PubMed and guidelines from pediatric societies. Standardized descriptors (MeSH) were used, prioritizing systematic reviews, clinical consensus statements, and cohort studies related to the diagnosis of pediatric asthma. Results: The diagnosis of asthma in children is based on the association between suggestive clinical history, evidence of chronic obstruction, and objective confirmation of airflow variability. In children >6 years old, spirometry is the main diagnostic test, while in children <5 years old the diagnosis is predominantly clinical with the aid of predictive indices. Symptoms such as nocturnal cough, wheezing, and dyspnea are fundamental, in addition to identifying risk factors such as family history, atopy, and viral infections. Biomarkers, such as exhaled nitric oxide, and functional assessments complement the diagnostic investigation. Conclusion: The diagnosis of pediatric bronchial asthma requires a careful and individualized clinical approach, considering the variability of symptoms and associated factors. Early identification and appropriate management are paramount to reducing exacerbations, preserving pulmonary function, and improving the quality of life of patients.